2019
DOI: 10.11591/ijeecs.v13.i3.pp892-901
|View full text |Cite
|
Sign up to set email alerts
|

Ring oscillator physically unclonable function using sequential ring oscillator pairs for more challenge-response-pairs

Abstract: <span>The ring oscillator physically unclonable function (ROPUF) is one of the several types of PUF that has great potential to be used for security purposes. An alternative ROPUF design is proposed with two major differences. Firstly, the memristor is included in the ring oscillators as it is claimed to produce a more random oscillation frequency. Other reasons are its memory-like properties and variable memristance, relative compatibility with CMOS, and small size. Secondly, a different method of gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In study [76], on the RO-PUF, two major modifications are suggested. The first modification is the addition of the memristor to the RO's inverting units, and the second is a change in how the PUF's response is generated.…”
Section: Implementation Of Memristive Puf (M-puf)mentioning
confidence: 99%
“…In study [76], on the RO-PUF, two major modifications are suggested. The first modification is the addition of the memristor to the RO's inverting units, and the second is a change in how the PUF's response is generated.…”
Section: Implementation Of Memristive Puf (M-puf)mentioning
confidence: 99%
“…To lower the circuit size and rate of power consumption, the ring oscillator inverter is incorporated with a memristor. [ 96 ] Thus, the number of challenge‐response pairs (CRPs) can be amplified without enhancing the circuit overhead.…”
Section: Applicationsmentioning
confidence: 99%
“…Reproduced with permission. [96] Copyright 2019, Institute of Advanced Engineering and Science. subsequently enhances the number of CRPs, reduces the complementary excitation of hackers, and enhances the time cost of the attackers, thereby preventing attacks.…”
Section: Nano-ppuf Based On Memristor Crossbarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Indonesian J Elec Eng & Comp Sci ISSN: 2502-4752 Ì 1393 the identification and authentication process must exist to ensure secure node-to-node and node-to-base station communications. Physical unclonable function (PUF) is a promising hardware fingerprinting technology that can be used in identification and authentication application [1]. PUF exploits the intrinsic process variations during integrated circuit (IC) fabrication to generate a device-specific response [2].…”
Section: Introductionmentioning
confidence: 99%